Role of the professional critical care team in improving the quality of critical care in the hospital (危重症专业小组在提升医院危重症护理水平中的作用探讨) - PENG Jine (彭金娥); WANG Siyi (王思懿); WU Xuehua (吴雪花) (中西医结合护理)
Objective To explore the role of a professional critical care team in improving the quality of critical care in the hospital. Methods The critical care team in the hospital was dominated by the ICU, and at the same time, a key nurse was selected from other departments to form a professional critical care team. The work situation of year 2020 and its influence on the quality of critical care were recorded. Results After the training, the quality assessment of critical care, nursing satisfaction with the professional critical care team and the qualified rate of oral care of the patients with mechanical ventilation were significantly higher than those before the training (P＜0. 05). According to the statistics of the work of the critical care professional team in 2020, 95 times of consultations, 4 times of general nursing training, 10 times of training for N3-grade nurses, 35 times of multidisciplinary nursing rounds and 300 times of department visits were conducted, respectively. Conclusion A professional critical care team can improve the quality of nursing, improve nursing satisfaction, and promote the level of intensive care. (目的 探讨危重症专业小组在提升医院危重症护理水平中的作用。方法 医院危重症专业护理小组由ICU主导, 同时在其他科室选择1名护理骨干共同组成。记录2020年度工作情况, 评价危重症专业小组对重症护理质量的影响。结果 培训后, 危重症护理质量考核、危重症专业小组护理满意度、机械通气患者口腔护理合格率均高于培训前(P＞0. 05)。对2020年度危重症专业小组的工作情况进行统计, 会诊次数为95次, 全员护士培训4次, N3级护士培训10次, 多学科护理查房35次, 出科访视300人次。结论 成立危重症专业小组可提升危重症专科护理质量, 提升护理满意度, 促进重症护理水平的提升。)